Factors to facilitate private developers in financing affordable housing for low-income group in Klang Valley / Norazmawati Md. Sani @ Abd. Rahim and Muhammad Shafiq Kamaruddin - Md. Sani @ Abd. Rahim, Norazmawati; Kamaruddin, Muhammad Shafiq (Universiti Teknologi MARA, Perak, 2023)
Affordable housing has become the main issue of concern among Malaysians, especially those from low-income background in Klang Valley. Limited housing supply in key areas within Klang Valley due to no interest from private developers has forced low-income people to live far from their workplaces. It is considered unprofitable by many private developers because of heavily regulated policies sanctioned by the government, decentralization of affordable housing agencies, and requiring specific design, which can drive the cost of development. Furthermore, access to home financing for low-income people is limited due to their current economic situation and financial constraints. The research focuses on the factors to facilitate private developers in financing and the possibility for the private developers to venture into a home financing structure and analyze other possibilities and solutions that can be implemented with the collaboration between the developers and government.